On the sidelines? The relationship between perceptions of inequality and political participation - Marius R. Busemeyer; Felix Jäger; Sharon Baute (University of Konstanz, Cluster of Excellence "The Politics of Inequality", Das Progressive Zentrum e.V., 2025)
This policy paper explores the relationship between perceptions of political efficacy and economic inequality. The latest findings from the Konstanz Inequality Barometer show that many people feel they have little influence on political decision-making and perceive political institutions as being unresponsive to their needs. As a result, they feel politically sidelined. The study identifies clear statistical correlations between perceptions of political efficacy and economic inequality. The paper concludes with concrete policy recommendations for (re)strengthening political participation.
Keywords: 320